2018
DOI: 10.1186/s12974-018-1307-1
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing study in patients with multiple sclerosis reveals variants associated with disease course

Abstract: BackgroundIt remains unclear whether disease course in multiple sclerosis (MS) is influenced by genetic polymorphisms. Here, we aimed to identify genetic variants associated with benign and aggressive disease courses in MS patients.MethodsMS patients were classified into benign and aggressive phenotypes according to clinical criteria. We performed exome sequencing in a discovery cohort, which included 20 MS patients, 10 with benign and 10 with aggressive disease course, and genotyping in 2 independent validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…In addition, the study of multi-incident MS families have nominated pathogenic mutations in NLRP1 , and purinergic receptors P2RX4 / P2RX7 which initiate inflammasome formation by modifying intracellular calcium and potassium concentrations [10, 11]. Rare missense variants in NLRP5 and NLRP9 have also been found to correlate with disease course and severity in MS patients [8, 56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the study of multi-incident MS families have nominated pathogenic mutations in NLRP1 , and purinergic receptors P2RX4 / P2RX7 which initiate inflammasome formation by modifying intracellular calcium and potassium concentrations [10, 11]. Rare missense variants in NLRP5 and NLRP9 have also been found to correlate with disease course and severity in MS patients [8, 56].…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the inflammasome has been proposed as a mechanism of autoimmunity in MS patients [156], a hypothesis that is supported by rare variants in inflammasome components NLRP1 , NLRP3 , NLRP5 and NLRP9 which were identified in MS families, or found to correlate with disease course and severity [8, 11, 54, 56]. In this study we describe two missense substitutions in NLRP12 , a NOD-like receptor family member that negatively regulates inflammation and NF-κB signaling, while promoting T-cell activation and differentiation [53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that several variants in NLRP9 may influence the disease course in multiple sclerosis patients, as determined by an exome sequencing study [19], and may be associated with familial late-onset Alzheimer's disease, as determined by a genome-wide association study [20]. However, little has been found regarding its effects on litter size.…”
Section: Association Analyses Of Nlrp5 and Nlrp9mentioning
confidence: 99%
“…Não representando apenas risco à EM, os genes HLA também podem estar envolvidos na proteção, como é o caso do gene HLA-A201 (BOQUETT et al, 2018;MOHAJER et al, 2018). Recentemente, estudo demonstrou que o sequenciamento do exoma de pacientes com esclerose múltipla revelou variantes associadas com o curso da doença (GIL-VAREA et al, 2018).…”
Section: Etiologia E Patologiaunclassified